1 × 2 × 8 1 + 2 × 3 × 9 1 + … + 9 9 × 1 0 0 × 1 0 6 1 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Please help .How did you reach to second step directly, can you teach if any such method exist to resolve such expression.
Log in to reply
I have provided the explanation in the revised solution.
I used programming in Java, this was the script.
class Pattern
{
static void pattern()
{
double sum=0,i;
for(i=1;i<=99;i++)
{
sum+=1/(i (i+1) (i+7));
}
System.out.print(sum);
}
}
I am sorry ,I don't know how to use Latex
Problem Loading...
Note Loading...
Set Loading...
Let the expression by S , then we have:
S = k = 1 ∑ 9 9 k ( k + 1 ) ( k + 7 ) 1 By partial fractions (see Note) = 4 2 1 k = 1 ∑ 9 9 ( k 6 − k + 1 7 + k + 7 1 ) = 4 2 1 k = 1 ∑ 9 9 ( k 6 − k + 1 6 − k + 1 1 + k + 7 1 ) = 4 2 1 ( k = 1 ∑ 9 9 k 6 − k = 1 ∑ 9 9 k + 1 6 − k = 1 ∑ 9 9 k + 1 1 + k = 1 ∑ 9 9 k + 7 1 ) = 4 2 1 ( 6 [ k = 1 ∑ 9 9 k 1 − k = 2 ∑ 1 0 0 k 1 ] − k = 2 ∑ 1 0 0 k 1 + k = 8 ∑ 1 0 6 k 1 ) = 4 2 1 ( 6 [ 1 1 − 1 0 0 1 ] − 2 1 − 3 1 − 4 1 − 5 1 − 6 1 − 7 1 + 1 0 1 1 + 1 0 2 1 + 1 0 3 1 + 1 0 4 1 + 1 0 5 1 + 1 0 6 1 ) ≈ 0 . 1 0 5
Partial Fractions
Assuming the following:
k ( k + 1 ) ( k + 7 ) 1 ⟹ 1 = k A + k + 1 B + k + 7 C = A ( k + 1 ) ( k + 7 ) + B k ( k + 7 ) + C k ( k + 1 )
Putting ⎩ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎧ k = 0 k = − 1 k = − 7 ⟹ 7 A = 1 ⟹ − 6 B = 1 ⟹ 4 2 C = 1 ⟹ A = 7 1 ⟹ B = − 6 1 ⟹ C = 4 2 1
⟹ k ( k + 1 ) ( k + 7 ) 1 = 4 2 1 ( k 6 − k + 1 7 + k + 7 1 )